A theory on merger timing and announcement returns - Pereira, Paulo J. (2015)
This paper develops a dynamic model for the timing and terms of mergers and acquisitions. In contrast to other models, we show that firms agree about the timing independently from how the merger surplus is shared. Firms agree on the timing and discuss the sharing rule of the merger surplus according to their bargaining power or some other exogenous factor. We also show that, under asymmetric information, the combination of surprises regarding merger timing and merger terms, can produce either negative or positive abnormal returns for the merging firms.